2022
DOI: 10.1021/acs.jpca.2c00306
|View full text |Cite
|
Sign up to set email alerts
|

Potential Catalytic Role of Small Heterocycles in Interstellar H2 Formation: A Laboratory Astrochemistry Study on Furan and Its Hydrogenated Forms

Abstract: It is now well-accepted in astrochemistry that the formation of interstellar H 2 is taking place on the surface of interstellar grains. It has also been suggested a long time ago that polyaromatic hydrocarbons (PAHs) can catalyze this process by subsequent H atom addition and H abstraction reactions. Recent quantum chemical computations suggested that small heterocycles can be better catalysts than PAHs. In this study, the reaction of H atoms with furan, 2,3-and 2,5-dihydrofurans, and tetrahydrofuran were stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 62 publications
0
1
0
Order By: Relevance
“…In this virtual special issue, N 2 O is reacted with C( 3 P), producing rate coefficients for such chemical processes, 21 and a similar study on fluoromethane and calcium atomic cations is also reported. 22 Additionally, the deuterated ethynyl radical is reacted with propylene producing a wealth of hydrocarbons, 23 NO + the propargyl radical generates branching ratios for eight common astrochemical products, 24 furan + H 2 reactions generate various c-C 4 H x O (x = 4−8) species, 25 myriad nitrous oxides are synthesized in H 2 O−N 2 O/N 2 ice mixtures, 26,27 dinitriles are shown to be produced from gas-phase reactions of cyano radicals and cyanoethane, 28 and porous amorphous solid water appears to catalyze interstellar organic chemistry. 29 From theory, the earliest molecule in the universe (HeH + ) is most efficiently rotationally excited by collisions with H 2 , 30 H 2 CCS and HCCSH are likely not detected since they are destroyed through barrierless reactions with atomic hydrogen, 31 and MgNC reacts with water clusters to produce the known HMgNC molecule along with other Mg-containing species.…”
mentioning
confidence: 99%
“…In this virtual special issue, N 2 O is reacted with C( 3 P), producing rate coefficients for such chemical processes, 21 and a similar study on fluoromethane and calcium atomic cations is also reported. 22 Additionally, the deuterated ethynyl radical is reacted with propylene producing a wealth of hydrocarbons, 23 NO + the propargyl radical generates branching ratios for eight common astrochemical products, 24 furan + H 2 reactions generate various c-C 4 H x O (x = 4−8) species, 25 myriad nitrous oxides are synthesized in H 2 O−N 2 O/N 2 ice mixtures, 26,27 dinitriles are shown to be produced from gas-phase reactions of cyano radicals and cyanoethane, 28 and porous amorphous solid water appears to catalyze interstellar organic chemistry. 29 From theory, the earliest molecule in the universe (HeH + ) is most efficiently rotationally excited by collisions with H 2 , 30 H 2 CCS and HCCSH are likely not detected since they are destroyed through barrierless reactions with atomic hydrogen, 31 and MgNC reacts with water clusters to produce the known HMgNC molecule along with other Mg-containing species.…”
mentioning
confidence: 99%